Strategies of Islamic Education Teachers in Creating an Inclusive and Child-Friendly Learning Environment: A Case Study at Imelda Health Vocational School in Medan - Zulfikar, Zulfikar; Tumiran, Tumiran (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to explore the strategies of Islamic Religious Education teachers in creating inclusive and child-friendly learning environments at Imelda Health Vocational School, Medan. The research is grounded in the challenges of student heterogeneity at the vocational level, which requires teachers to adopt adaptive, humanistic, and contextual strategies. Methodology: The research employed a qualitative approach with a descriptive method. Data were collected through direct observation of the learning process, in-depth interviews with Islamic Religious Education teachers, students, and the principal, as well as documentation of syllabi, lesson plans, and relevant school policies. Data analysis applied an interactive model consisting of data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and method triangulation. Main Findings: The findings reveal that Islamic Religious Education teachers integrate inclusive values through collaborative teaching methods, contextualization of subject matter with the field of health, and the use of simple technologies. Teachers also act as agents of transformation by fostering empathy, building student self-confidence, and cultivating child-friendly classroom environments. Institutional support strengthens these strategies, ensuring that Islamic Religious Education goes beyond cognitive aspects to include spiritual, social, and professional character development. Novelty/Originality of this study: The study underscores the significance of Islamic Religious Education as a medium for strengthening humanitarian values in vocational education. It demonstrates how inclusive strategies can transform learning spaces into holistic environments that shape students’ intellectual competence and moral identity.